(untitled) (ASEAN Engineering Journal, 2014)
The performance of a membrane module depends not only on the membrane properties but also on the operating conditions. Current efforts usually focus on the enhancement of membrane characterization, less attention has been paid to the process parameters in which the membrane itself should be operated. The decision on operating conditions is generally based on experience, looking on handbook or suggestion of membrane manufacturers. However, the transport equation governing the performance of the membrane system varies in particular application and situation. Therefore, a general procedure for the design and operation strategy should be introduced for any given application. In our previous study, a simple combined model was developed to predict the permeation in cross-flow ultrafiltration of protein solution. Then, the - steady state permeate flux was estimated from the model and the correlation to operating condition is established. From the governing equation, it should be possible to study the effect of operating condition on the cost for any given application. In this study, the configuration is assumed as feed and bleed operating mode and a model which incorporates the friction loss is introduced. Then, it is applied to investigate the effect of operating parameters such as the pressure and the recirculation flow rate to the average cost per unit volume permeate. The average cost is the cost per unit volume permeate of an existing module. The total cost includes a fixed component relating to the size of the existing module and the operating component associated with the energy usage. The simple optimization routine (cyclic coordinate method) is also used to determine the most cost effective module operation.